Mechanical Behavior of Loess Tunnels Caused by Surface Water Joints Infiltration - Qingfu Li; Ming Liu; Yingqiao Yu (Advances in Civil Engineering)
Many researchers have conducted a vast amount of research on water sensitivity and joint seepage in loess tunnels. However, studies on the mechanical effects of shallow buried loess tunnels under the influence of joint dominant seepage are still insufficient. In this study, we simulate the seepage range of loess tunnels with joints, and we use this seepage range to numerically simulate the mechanical properties of shallow buried loess tunnels. Studies have shown that the permeability coefficient and the number of joints are the key factors that affect the amount of surface water infiltration. An increase in the permeability coefficient on the order of 5 × 10−3 m/s will cause the surface water to pour into the ground and rapidly form a saturated soak zone on the liner, while an increase in the number of joints will increase the width and formation rate of the saturated zone. The results of the tunnel mechanics simulation show that the surface settlement and the surrounding rock displacement increase with the increase of the wetted area of the vault; the effect of arch footing water immersion on the surface settlement and the surrounding rock displacement is most significant for the same wetted area width. Compared with the three-stage method, the center cross diaphragm (CRD) method of excavation can better control the surface and the surrounding rock settlement under waterlogged conditions. In particular, the lining settlement on the waterlogged side can be effectively controlled, and the overall settlement of the tunnel is more uniform.